2018
DOI: 10.1111/febs.14686
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral diterpene cyclases show increased thermostability and substrate acceptance

Abstract: Bacterial diterpene cyclases are receiving increasing attention in biocatalysis and synthetic biology for the sustainable generation of complex multicyclic building blocks. Herein, we explore the potential of ancestral sequence reconstruction (ASR) to generate remodeled cyclases with enhanced stability, activity, and promiscuity. Putative ancestors of spiroviolene synthase, a bacterial class I diterpene cyclase, display an increased yield of soluble protein of up to fourfold upon expression in the model organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…This is a reasonable scenario, in particular since co-evolution may have led to the adaptation of the protein to the assistance machinery of its original host. Consequently, the fact that resurrected ancestral proteins often show improved heterologous expression as compared with their modern counterparts [22][23][24][25][26][27][28][29][30][31][32][33][34][35] plausibly reflects an ancient adaptation to unassisted folding. Efficient unassisted folding would no longer be a useful feature after the evolutionary emergence of cellular foldingassistance, thus allowing the evolutionary acceptance of mutations that impair the ancestral feature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a reasonable scenario, in particular since co-evolution may have led to the adaptation of the protein to the assistance machinery of its original host. Consequently, the fact that resurrected ancestral proteins often show improved heterologous expression as compared with their modern counterparts [22][23][24][25][26][27][28][29][30][31][32][33][34][35] plausibly reflects an ancient adaptation to unassisted folding. Efficient unassisted folding would no longer be a useful feature after the evolutionary emergence of cellular foldingassistance, thus allowing the evolutionary acceptance of mutations that impair the ancestral feature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a substantial number of studies have actually reported improved heterologous expression of ancestral proteins as compared with their modern counterparts. Examples include: phosphate-binding protein 22 , periplasmic binding protein 23 , serum paraoxonase 24 , coagulation factor VIII 25 , titin 26 , haloalkane dehalogenases 27 , cytidine and adenine base editors 28 , diterpene cyclase 29 , rubisco 30 , endoglucanases 31 , L-amino acid oxidases 32 , laccases 33 , front-end D6-desaturases 34 and fatty acid photo-decarboxylases 35 . On a related note, recent studies on ancestral proteins have noted an improved capability to yield crystals suitable for X-ray structural determination 36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…Consensus design relies on the simple analysis of the conservation of the amino acids on the individual positions in the sequence alignment. As a result, it cannot account for the coevolution of the residues located in the sites responsible for the protein’s activity [ 3 ] and is utilized mostly as a part of the hybrid workflows [ 4 , 5 ]. In comparison, ASR goes much further by also considering evolutionary information depicted by the phylogenetic tree.…”
Section: Introductionmentioning
confidence: 99%
“…Computational methods are important and prominent tools that can offer deep mechanistic insights into the complexity of biological systems [18–22] and become more powerful with the ongoing technical evolution of high‐performance computing resources [23,24]. In this work, the methods of bioinformatics, protein–protein/ligand docking, and molecular dynamics were applied to study the co‐operation between domains in the structure of NanA.…”
Section: Introductionmentioning
confidence: 99%